Concept of an Interdisciplinary University-Inter-Transdisciplinarity - Kulkarni, P. D. (Journal of Engineering Education Transformations, 2011)
This article is an attempt by the author to present to the readers of JEE a brief summary of the report: CERI "Interdisciplinarity - Problems of teaching and research in University, (1970) OECD.